2020
DOI: 10.31557/apjcp.2020.21.6.1511
|View full text |Cite
|
Sign up to set email alerts
|

Association of TP53 Codon 72 Arg>Pro Polymorphism with Breast and Lung Cancer Risk in the South Asian Population: A Meta-Analysis

Abstract: Background: A transversion missense polymorphism of the TP53 tumor suppressor gene at the codon 72 codes proline instead of arginine causes an altered p53 protein expression and has been found to be associated with an elevated risk of various cancer; especially breast and lung cancer. As the previous case-control studies on the South Asian population have shown controversial results, we performed a meta-analysis to evaluate a precise estimation of the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Overall, our findings showed that the dominant and additive models were associated with an increased risk of breast cancer for the carriers of 72Pro allele. These results corroborate with the data reported from two recent meta-analyzes, the first covering eleven studies with 950 cases and 882 controls in the Asian population [ 50 ] and the second performed on the Indian population which covered seven studies with 1249 cases and 1838 controls [ 51 ]. These authors in their analysis showed that the dominant and the additive models were associated with the risk of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our findings showed that the dominant and additive models were associated with an increased risk of breast cancer for the carriers of 72Pro allele. These results corroborate with the data reported from two recent meta-analyzes, the first covering eleven studies with 950 cases and 882 controls in the Asian population [ 50 ] and the second performed on the Indian population which covered seven studies with 1249 cases and 1838 controls [ 51 ]. These authors in their analysis showed that the dominant and the additive models were associated with the risk of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our ndings showed that the dominant and additive models were associated with an increased risk of breast cancer for the carriers of 72Pro allele. These results corroborate with the data reported from two recent meta-analyzes, the rst covering eleven studies with 950 cases and 882 controls in the Asian population [50] and the second performed on the Indian population which covered seven studies with 1249 cases and 1838 controls [51]. These authors in their analysis showed that the dominant and the additive models were associated with the risk of breast cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were present in this allele association with breast cancer. This was also confirmed by multiple studies where the carriers of the Arg72Pro allele were shown to have a higher risk of breast cancer in both the dominant and additive models compared to the wild type (wtTP53) (33,34). This would follow that because a significant percentage of breast cancer have p53 mutations, it is reasonable to posit that patients with bladder cancer as an index cancer that is also associated with p53 mutation on the same allele would have an increased incidence of breast cancer as a second primary malignancy.…”
Section: Discussionmentioning
confidence: 53%